O nível subliminar na percepção: os subsentidos da mensagem publicitária - Nascimento, Sônia Maria Moro do (2008)
The classical interpretation of Subliminal is that there is a powerful seduction and manipulation widened by the presence of some components placed below perception, which freely reach the subconscious level, to the point of affecting emotions. This happens because such messages go into the recipient s mind, beneath the threshold of his conscious alertness, without any filtering, so as to allow for the effects intended by the originating source to take the individual to act regardless of his own will and with no evaluation. Through the concepts of C. S. Peirce s semiotics, this study aims at understanding the functioning of the process of apprehension of subliminal materials in perception, and intends to contribute to the update of this concept by adding a semiotic direction and a treatment as a language study. Printed advertisements in nationwide magazines are analyzed to view the evidence they carry of the elements that are at stake in the articulation of visual and verbal elements, a play with signs which escape to the sight and perceptual judgment of the recipient. The concept of subliminal is discussed in the bases of the definitions of perception and perceptual judgment, with emphasis to the fact that the subliminal works as an apprehension underneath the perceptual judgment. The theoretical and methodological bases are enhanced by further definitions from Peirce s sign theory, covering the concepts of first, other phenomenological categories, triad sign structure, notion of consciousness, collateral experience, beyond the associations by similarity and contiguity as present in the various language approaches